Muhyiddîn İbnü'l-Arabî'de İdrîs peygamber - Akkaya, Veysel (My University, 2009)
Hakîm (Bilge), Kutub, Gelenek, Kâmil İnsan, Yükseliş, Güneş feleği, Tenzîh, Ârif, Seyr u sülûk, Kalb ÖZET MUHYİDDÎN İBNÜ’L-ARABÎ’DE İDRÎS PEYGAMBER Bütün kültür ve medeniyetlerde varlığını sürdüren Gelenek’in (Tradition) pîri olan ve “Hermeslerin Hermesi” olarak bilinen Hz. İdrîs’i, tasavvufun büyük üstadlarından Muhyiddîn İbnü’l-Arabî, nebevî şahsiyeti, metafizik hakîkati ve sûfîlere bıraktığı mîrâs açısından anlatmıştır. Hz. İdrîs’in semâya yükselişlerinin; İdrîs peygamber açısından netîceleri, mârifet-i ilâhiye ve sâlik açısından neler ifâde ettiği üzerinde durmuştur. İbnü’l-Arabî’ye göre Hz. İdrîs, peygamberliği yanında Hak tarafından kendisine öğretilen birçok ilmi ve hikmetleri insanlığa mîrâs bırakan bir “hakîm”(bilge), Allah Teâlâ’nın Güneş feleğine rûh ve bedenle yükselterek, Hz. Muhammed’e vekâleten âlemin hükümdârı yaptığı en büyük “kutub”; ölmemiş fakat bedeni rûhânîleşmiş bir şekilde yaşayarak, Hz. Âdem ile başlayıp Hz. Peygamber ile zirveye ulaşan “hanîf dîni”n devâm etmesinde görevli “kâmil insan”, mârifetullahta (tenzîh açısından) yüce bir mertebeye sâhip “ilk ârif”tir. Yine ona göre “Hz. İdrîs”, bedeniyle yaşamaya devâm ederken, “Hz. İlyâs” olarak ikinci kez yaratılan ve bu bedeniyle de hâlen rûhânîleşmiş bir şekilde hayatta olan müstesnâ bir şahsiyet ve seyr u sülûk yaparken yüce bir mertebe olan “kalb makāmı”na yükselişte sûfîlere mükemmel bir rehberdir. KEY WORDS: Hakīm (Wise), Qutb, Tradition, al-Insan al- Kamil (Perfect Human Beings), Ascension, Sphere of sun, Tanzīh (Consideration of free from defects), Ārif (Gnostic), Sayrsulūk (Special training of the Sufis), Heart

PROPHET ENOCH IN THE WORKS OF MUHYIDDĪN B. ARABĪ Sufi master Muhyiddin b. Arabī deals with the Prophet Enoch, who is the father of the Tradition and is known as “Hermes of the Hermeses”, from the points of his prophetic personality, metaphysics reality, and his heritage left for the Sufis. Ibn Arabī also talks about Enoch’s ascensions to heaven; consequences of these ascensions for the prophet Enoch; and what they mean in respect to Divine knowledge and dervishes. According to Ibn Arabī, in addition to being a prophet, Enoch was also a “hakīm ” or a wise person, who left humanity the knowledge and wisdom taught him by God. God elevated Enoch physically and spiritually to the sphere of sun and made him the greatest Qutb of the universe by proxy to the Prophet Muhammad. He did not die but lived with his spiritualized body. He was the appointed insān al- kamil or the perfect human being for the continuation of the religion of Ḥanīf, which began with Adam and reached its apex with the prophet Muhammad. He was the first Gnostic, who had a high station in respect to Divine knowledge. According to Ibn al-Arabī, the prophet Enoch, who was revived in the body of Elijah while he was still living in the body of Enoch, was an exceptional personality and he is a perfect guide for the Sufis who are in their mystical training to reach the high station of heart.
Keywords: İslam Dini; Peygamberler; Tasavvuf